Compound specific carbon and hydrogen stable isotope analyses of volatile organic compounds in various emissions of combustion processes - Vitzthun von Eckstaedt, C.; Grice, Kliti; Ioppolo-Armanios, M.; Kelly, David; Gibberd, Mark (Elsevier, 2012)
This study presents carbon (δ13C) and hydrogen (δD) isotope values of volatile organic compounds (VOCs) in various emission sources using thermal desorption–gas chromatography–isotope ratio mass spectrometry (TD–GC–irMS). The investigated VOCs ranged from C6 to C10. Samples were taken from (i) car exhaust emissions as well as from plant combustion experiments of (ii) various C3 and (iii) various C4 plants. We found significant differences in d values of analysed VOCs between these sources, e.g. δ13C of benzene ranged between (i) -21.7 ± 0.2‰, (ii) -27.6 ± 1.6‰ and (iii) -16.3 ± 2.2‰, respectively and δD of benzene ranged between (i) -73 ± 13‰, (ii) -111 ± 10‰ and (iii) -70 ± 24‰, respectively. Results of VOCs present in investigated emission sources were compared to values from the literature (aluminium refinery emission). All source groups could be clearly distinguished using the dual approach of δ13C and δD analysis. The results of this study indicate that the correlation of compound specific carbon and hydrogen isotope analysis provides the potential for future research to trace the fate and to determine the origin of VOCs in the atmosphere using thermal desorption compound specific isotope analysis.